Evaluating the impact of urolithin a supplementation on running performance, recovery, and mitochondrial biomarkers in highly trained male distance runners - Whitfield, J.; McKay, A. K. A.; Tee, N.; McCormick, R.; Morabito, A.; Karagounis, L. G.; Fouassier, A. M.; D`Amico, D.; Singh, A.; Burke, L. M.; Hawley, J. A. (Sports Medicine, 2025)
Background: Urolithin A (UA) is a metabolite produced by gut bacteria following the consumption of ellagitannin-rich foods. Clinical trials in middle-aged and older adults demonstrated that supplementation with UA improves muscle strength, endurance, and biomarkers of mitochondrial health, suggesting that UA may be an effective ergogenic aid in other populations. Methods: In this double-blind, parallel group, placebo-controlled clinical trial (NCT04783207), competitive male distance runners (n = 42, 27.2 ± 1.0 years, 66.4 ± 0.6 mL·kg-1·min-1, mean ± SEM) were randomized to consume either 1000 mg·day-1 UA (n = 22) or placebo (PL; n = 20) for 4 weeks during an altitude training camp (~ 1700-2200 m). Physiological outcomes including body composition, hemoglobin mass, running economy, and maximal aerobic capacity (VO2max) were measured in all subjects at baseline and at the end of the 4-week camp to assess training- and supplementation-induced adaptations. During the camp, a weekly downhill running bout was performed to challenge skeletal muscle, with capillary blood samples collected to assess inflammation (C-reactive protein; CRP) and indirect markers of muscle damage (creatine kinase; CK). A subset of athletes also either completed a 3000 m track time trial (n = 11 PL, n = 11 UA) or had skeletal muscle biopsies taken (n = 9 PL, n = 11 UA) pre/post supplementation to determine the effect of UA on running performance and for exploration of alterations in skeletal muscle proteome and mitochondrial function, respectively. Results: Running performance (3000 m time trial) was not significantly improved in either treatment group (UA; p = 0.116, PL; p = 0.771), although UA supplementation significantly lowered ratings of perceived exertion (RPE, p = 0.02) and reduced indirect markers of post-exercise muscle damage (CK, total area under the curve p < 0.0001) following the 3000 m time trial compared with PL. Although there was no statistically significant time × treatment interaction for aerobic capacity (p = 0.138), UA supplementation showed a large within-group increase in VO2max (5.4 ± 0.9%, 66.4 ± 0.8 to 70.0 ± 1.0 mL·kg-1·min-1, p = 0.009, d = - 0.83), with a smaller increase in the PL group (3.6 ± 1.3%, 66.4 ± 0.9 to 68.7 ± 1.0 mL·kg-1·min-1, p = 0.098, d = - 0.54). Proteomic screening of skeletal muscle biopsies revealed UA upregulated pathways associated with mitochondria, while downregulating inflammatory pathways. While not statistically significant, UA led to a medium effect for increased markers of mitophagy (d = - 0.74), without changes in mitochondrial function. Conclusions: Our results show that 4 weeks of daily UA supplementation facilitates recovery by downregulating inflammatory pathways and indirect markers of muscle damage. However, despite a reduction in rating of exertion and increased aerobic capacity, UA supplementation did not further enhance performance in highly trained male endurance athletes.